2019
DOI: 10.1038/s41416-019-0610-7
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D2 in prostate cancer: protein expression changes with Gleason score

Abstract: Background Phospholipases D1 and D2 (PLD1/2) are implicated in tumorigenesis through their generation of the signalling lipid phosphatidic acid and its downstream effects. Inhibition of PLD1 blocks prostate cell growth and colony formation. Here a role for PLD2 in prostate cancer (PCa), the major cancer of men in the western world, is examined. Methods PLD2 expression was analysed by immunohistochemistry and western blotting. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 111 publications
3
8
0
Order By: Relevance
“…The unique and scarce patient-derived primary PCa cells used here, as in our earlier work 9,24 , have a basal cell phenotype (CK5 + / CK8 -/ AR -/ CD49b + / CD44 + / CD24 + ) 45,46 . These are the main cells cultured from PCa biopsy tissue because tumorigenic luminal cells which account for the bulk of PCa tissue do not adapt to culture as they are terminally differentiated.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The unique and scarce patient-derived primary PCa cells used here, as in our earlier work 9,24 , have a basal cell phenotype (CK5 + / CK8 -/ AR -/ CD49b + / CD44 + / CD24 + ) 45,46 . These are the main cells cultured from PCa biopsy tissue because tumorigenic luminal cells which account for the bulk of PCa tissue do not adapt to culture as they are terminally differentiated.…”
Section: Discussionmentioning
confidence: 83%
“…The PC3 prostate epithelial cell line was cultured as described in Noble et al 9,24 . Primary PCa epithelial cells were purified from human prostate tissue samples which were obtained with patient consent and full ethical approval (South Yorkshire Research Ethics Committee, Yorkshire and the Humber, REC:07/H1304/121) as previously stated 24 .…”
Section: Cell Isolation and Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is suggested that PLD1 might confer resistance to HDAC inhibitors. It has been reported that inhibition of PLD2 has therapeutic potential against cancers [ 31 34 ]. Herein, we show that PLD2 is upregulated by HDAC inhibitors in a transcriptional level.…”
Section: Discussionmentioning
confidence: 99%